2003
DOI: 10.1023/a:1024037100696
|View full text |Cite
|
Sign up to set email alerts
|

The effects of British and American trial procedures on the quality of juror decision-making.

Abstract: Compared to American trial procedures, British procedures provide a less distracting environment in which jurors can process trial evidence. Relying on theories of persuasion, it was predicted that jurors viewing British procedures would be less affected by extra-evidentiary cues and would be more sensitive to evidence strength variations than jurors in American trials. Participants (N = 245) viewed a mock trial in which trial procedure, judge's nonverbal behavior, and evidence strength were varied. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Without trying to settle a debate that involves much broader issues than the ones analyzed here, our analysis provides a clear policy implication for the current system of juror decision-making: procedural rules governing the adjudicative process should be targeted at enhancing jurors recall. For example, it has been shown that giving preliminary instructions on the applicable law (ForsterLee and Horowitz, 2003), notetaking (Rosenhan et al, 1994;ForsterLee and Horowitz, 2003), providing notebooks with relevant trial documents (Dann et al, 2004), and Judge's summation and direct questioning of witnesses (Collet and Kovera, 2003) enhance a juror's ability to process and recall relevant evidence. Similarly, in light of our result that cumulative evidence may strengthen jurors' beliefs in a given hypothesis, particular attention should be paid to evidence rules regarding the relevancy of the information presented during trial and, in particular, the exclusion of cumulative evidence (e.g., rule 403, Federal Rules of Evidence).…”
Section: Jurors' Delusions: the Verdict After An Infinite Number Of Smentioning
confidence: 99%
“…Without trying to settle a debate that involves much broader issues than the ones analyzed here, our analysis provides a clear policy implication for the current system of juror decision-making: procedural rules governing the adjudicative process should be targeted at enhancing jurors recall. For example, it has been shown that giving preliminary instructions on the applicable law (ForsterLee and Horowitz, 2003), notetaking (Rosenhan et al, 1994;ForsterLee and Horowitz, 2003), providing notebooks with relevant trial documents (Dann et al, 2004), and Judge's summation and direct questioning of witnesses (Collet and Kovera, 2003) enhance a juror's ability to process and recall relevant evidence. Similarly, in light of our result that cumulative evidence may strengthen jurors' beliefs in a given hypothesis, particular attention should be paid to evidence rules regarding the relevancy of the information presented during trial and, in particular, the exclusion of cumulative evidence (e.g., rule 403, Federal Rules of Evidence).…”
Section: Jurors' Delusions: the Verdict After An Infinite Number Of Smentioning
confidence: 99%
“…In a courtroom setting, the trial judge is seen by jurors as a high‐authority figure (Feldmann & Bell, 1993) and as such as a credible source of information and guidance with respect to evaluating evidence. Indeed, Collett and Kovera (2003) reported that even non‐verbal judicial behaviour had a substantial effect on mock jurors' evaluations of the defendant's liability and responsibility. A fortiori , we predict that verbal messages from the judge will impact how mock jurors' process information, including how they evaluate the credibility of a child witness.…”
mentioning
confidence: 99%